Beta-glucans induce cellular immune training and changes in intestinal morphology in poultry - Bar-Dagan, Hadar; Gover, Ofer; Cohen, Natalie Avital; Vetvicka, Vaclav; Rozenboim, Israel; Schwartz, Betty (Frontiers in Veterinary Science, 2023)
Beta-glucans are known as biological response modifiers due to their ability to activate the immune system. This research aimed to determine the efficacy and safety of feeding beta-glucans from various sources on the immune status and intestinal morphology of chickens. To this end we used in vitro and in vivo set-ups. In the in vitro set-up the chicken macrophage cell line HD-11 was used to measure the response of the chicken immune cells to beta-glucans extracted from algae and mushrooms on immune-related gene expression and associated activities. Additionally, we conducted two in vivo experiments using either beta-glucans extracted from yeast or mix of yeast and mushrooms beta-glucans as part of the chicks feed in order to test their effects on the chick intestinal morphology. In the in vitro set-up exposure of HD-11 cells to a concentration of 1 mg/ml of algae and mushroom beta-glucans resulted in significantly higher expression of 6 genes (TNFɑ, IL4, IL6, IL8, IL10, and iNOS2) compared to control. The release of nitrite oxide (NO) to the medium after exposure of HD-11 cells to mushrooms or algae beta-glucans was significantly increased compared to control. Additionally, significantly increased phagocytosis activity was found after exposure of the cells to algae and mushroom beta-glucans. In the in vivo set-up we observed that the length of the villi and the number of goblet cells in the ileum and the jejunum in the beta-glucan fed chicks were significantly augmented compared to control, when the chicks were fed with either yeast or yeast and mushroom beta-glucans mix. In conclusion, dietary supplementation of poultry with beta-glucan exerts significant and positive effects on immune activity and the intestinal morphology in poultry.